Differences between body characteristics, motor skills and functional capacities among young male and female rowers - Kunac, M.; Šeper, V.; Nešic, N.; Davidovic Cvetko, E. (1st International Scientific Conference 4 Healthy Academic Society: Proceedings, 2023)
Rowing is a sport that involves propelling a boat through water using one or more oars. Examining the contrasting traits of male and female rowers, identifying variances and commonalities in anthropometric attributes that can impact not only training protocols but also serve as cues for talent identification programs, holds significant significance in the realm of rowing. The participants were members of the Croatian Rowing Club Vukovar from Vukovar. The sample consisted of 19 rowers (11 boys, 8 girls). Statistically significant differences by gender were found only for forced expiratory volume in 1 second (FEV1) and maximal voluntary ventilation (MVV) values. Male participants had significantly higher FEV1 values compared to female participants (mean difference (MD) = +0.84; p = 0.045). MVV values were also significantly higher in males compared to females (MD = +36.22; p = 0.01). There were no statistically significant differences between male and female participants in the results obtained by bioelectrical impedance (p > 0.05). There were statistically significant differences between male and female participants on flexibility and strength tests. Male participants had significantly lower values on the flexibility test (MD = -9.58; p = 0.04), while they had significantly higher values on the number of squats in one minute (MD = +12.70; p = 0.000) compared to female participants.